Konversi Gliserol menjadi Polihidroksibutirat dengan Menggunakan Bakteri Eschericia coli - Rahayu, Endah Fitriani; Trisunaryanti, Wega; Wijaya, Karna (Universitas Negeri Semarang, 2017)
Conversion of glycerol into polyhydroxybutyrate (PHB) using Eschericia coli bacteria had beed evaluated. The bacteria was cultured in lactose medium, consist of 1% of lactose, peptone, and NaCl, then incubated at 37oC for 24 h. The bacteria culture was then added into the 10 g/L, 20 g/L, 30 g/L, 40 g/L, and 50 g/L glycerol media and then fermented for 24, 48, 72, and 6 h, then followed by centrifugated and solid phase was dried and weighed as a biomass. The filtrate was analyzed to determine the remaining glycerol. PHB was extracted from the biomass using chloroform, and then analyzed by FT-IR, H-NMR, C-NMR and viscometer. Monomer unit of the polymer was produced by esterification of the polymer then analyzed by GC. Analysis generates that FT-IR, H-NMR, C-NMR, and GC shows the PHB can be synthesize from glycerol using Eschericia coli. PHB production is increasing if the time fermentation and initial glycerol concentration has been risen, with the maximum PHB produced is 92,73%. Molecular weight of PHB has maximum value if produced at initial glycerol concentration 40 g/L for 96 h. in the initial glycerol concentration 50 g/L, the molecular weight of PHB was reduced.